2017
DOI: 10.1155/2017/9842450
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Modeling of Patient and Physician Determinants of Blood Pressure Outcomes in Hypertensive Patients with and without Diabetes: Pooled Analysis of Six Observational Valsartan Studies with 15,282 Evaluable Patients

Abstract: We pooled data from 6 valsartan-related studies including 3,658 diabetic and 11,624 nondiabetic patients to evaluate blood pressure (BP) outcomes after approximately 90 days of second- or later-line valsartan treatment. Hierarchical linear and logistic regressions were applied to identify determinants of BP outcomes. Similar reductions in BP values and similar BP control rates were achieved in both groups after approximately 90 days of therapy. The modeling analyses identified several common and different pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Finally, several of the included studies reported large variations at the physician level that could not be attributable to observable measures, such as age or years of experience. 26 30 37 42 55 56 59 Physician-level individual variation is thus an important cause of disparities in healthcare quality, and explaining this variation through measures other than age or years of experience will be important in eventually addressing quality gaps.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, several of the included studies reported large variations at the physician level that could not be attributable to observable measures, such as age or years of experience. 26 30 37 42 55 56 59 Physician-level individual variation is thus an important cause of disparities in healthcare quality, and explaining this variation through measures other than age or years of experience will be important in eventually addressing quality gaps.…”
Section: Discussionmentioning
confidence: 99%